The influence of synoptic weather regimes on UK air quality: analysis of satellite column NO2. (6th March 2014) - Pope, R. J.; Savage, N. H.; Chipperfield, M. P.; Arnold, S. R.; Osborn, T. J.
Abstract Groupings of Lamb weather types (LWTs) are used to assess the influence of synoptic meteorology on UK tropospheric column NO2. Composite satellite maps using daily 2005–2011 data show significant NO2 anomalies for each group. Hence, despite large day‐to‐day variability and significant uncertainty in individual retrievals, the satellite data can be used to determine national‐scale column NO2 variations under different meteorological conditions. Under cyclonic conditions, NO2 is reduced, while anticyclonic conditions aid its accumulation, especially during winter, consistent with trapping of surface emissions and slower photochemical processing. This composite dataset can be used to test seasonal simulations of air quality models.